Drug Metabolism - Dunnington, Katherine (IntechOpen, 2021)
Drug metabolism comprises the identification, characterization, and quantification of the chemicals or compounds produced in an animal or human upon administration of a drug. Research practices not only require the chemical structure but also aim to determine the pharmacological activities and/or toxicity of these compounds. This is first performed in animals, as studies attempt to identify and quantify metabolites, and later in humans, with care to further characterize metabolites that are either unique to or produced disproportionately in humans compared to animals. Characterization includes the determination of enzyme systems or other biological mechanisms that produce each identified metabolite; this information is used to predict potential drug-drug interactions with other compounds that increase or decrease metabolite formation and sources of biological variability in response or toxicity with varying patient genetics, which affect CYP isoform expression. This book's purpose is to provide some understanding of the biology and current technology applied in the field of drug metabolism.